The Effect of Differentiated Learning on EFL Students’ Reading Skills - Indi Azimah; Wahyu Diny Sujannah (Didaktika: Jurnal Kependidikan, 2024)
Students might have different levels of reading skills due to their knowledge and background. Implementing differentiated learning can be a solution to overcome this diversity by helping them face challenges and achieve good reading comprehension in 21st-century education. This pre-experimental research aimed to explore the effect of differentiated learning on students’ reading skills. The application of this strategy focused on the aspects of process, content, and product differentiation. The participants were 29 eighth-grade students from one of the State Junior High Schools in Batu. The results indicate that implementing differentiated learning is effective in improving students’ reading skills since it helps them face challenges in reading, learn more vocabulary, provide a fun reading experience, and achieve learning objectives. Hence, it is suggested that English teachers implement differentiated learning to teach reading. Moreover, future research may explore students’ difficulties while implementing differentiated learning to learn reading.